Cognitive Function of Elderly Persons in Japanese Neighborhoods: The Role of Street Layout. Issue 6 (September 2019) - Koohsari, Mohammad Javad; Nakaya, Tomoki; McCormack, Gavin R.; Shibata, Ai; Ishii, Kaori; Yasunaga, Akitomo; Oka, Koichiro
Objectives: The aims of this study were to examine (a) associations of two metric and space syntax measures of street layout with the cognitive function of Japanese older adults and (b) the extent to which objectively assessed physical activity mediated such associations. Methods: Cross-sectional data from 277 older adults who lived in Japan were used. Street layout attributes were objectively calculated for each participant's geocoded home location. The Mini-Mental State Examination was used to evaluate cognitive function. Physical activity was objectively assessed with accelerometers. Results: There was a statistically significant negative association between street integration and the odds of having cognitive impairment. Objectively assessed physical activity did not attenuate this relationship. Conclusions: Our findings provide unique evidence regarding the importance of the topological aspects of street layouts in (re)designing neighborhoods to support mental illness.